Assessment of Groundwater Drinking Sources in Eku and Its Environs, in the Niger-Delta Region of Nigeria (Baghdad Science Journal, 2022)
This study assessed the quality of hand-dug drinking water sources in Eku and its environs at Eku I, Samagidi, Eku 2, and Okuechi, using the weighted arithmetic water quality index method. Water samples collected from hand-dug wells at these locations returned values for analyzed parameters. Temperature 26 – 30(⁰C), dissolved Oxygen (D.O) 5.2-8mg/l, biological oxygen demand (BOD) 5.2-8(mg/l), Electrical Conductivity (EC) 77-119(µS/cm), Total suspended solids were  (TSS) 20000-120000(mg/l), pH 5.31-7.09, Phosphates 2-9.2(mg/l), Alkalinity 28-160(mg/l), Turbidity, 0.02 -0.19(NTU) Total coliform 2 -48 (cfu/ml) and fungal count 1-502. Variations in the values of these parameters were only significant for phosphate, alkalinity, and turbidity between Samagidi and Okuechi at a level of significance of p≤0.05. D.O, BOD, phosphates, total coliform and TSS levels, exceeded standards recommended by NSDWQ/WHO, rendering these water sources unsuitable for drinking purposes. Cluster analysis revealed three cluster groups; cluster 1(Eku2), cluster 2(Samagidi), and cluster 3(Eku1 and Okuechi), while factor analysis showed a strong correlation with pH, D.O, BOD, phosphate, conductivity, total coliform and fungal counts with water sources in the study stations. The calculated WQI for these water sources is 107.56, 95.18, 103.45, and 110.36 for Eku I, Samagidi, Eku 2, and Okuechi, respectively, classifying them as very poor water quality and unsuitable for drinking purposes. Indiscriminate waste disposal, surface runoff and poor sanitary facilities, and the exposed nature of these wells are major contributors to the deterioration of these wells.